THE EFFECT OF USING MAGNETIC PEFOMANCE WATER IN SOME TRAITS AWASSI LAMBS - Ahmad , Bashar Adham; Abdullah, Dhafir S. (Diyala Agricultural Sciences Journal, 2012)
This study was conducted at animal farm related to Animal Resources Department – College of Agriculture / University of Tikrit from 25-5-2010 to 15-7-2011 . In this study 45 Awassi ewes were used at the age 3-5 with primary weight 38.91 Kg . They were divided randomly in to three Groups each Groups having 15 ewes . The aim was to investigate the effect of using magnetic water ( 750 -1500 ) Gaus , dam age , month of Lamping , sex of born , and dam weight at Lamping on some economical aspects of the Lamb such as birth wt. , weaning wt. , pro weaning daily gain , 6 month wt. and post weaning daily gain . magnetic water has no significant effect ( p< 0.05 ) growth traits of Lambs but significant effect (p< 0.05 ) in post weaning daily gain , The age of the dam did not effect traits studied , while the month of Lambing has a significant effect ( p< 0.01 ) of 6 month wt. trait for lambs as compared with other lambs , birth's at November birth's at other month's also show significant effect ( p< 0.01 ) in pro weaning daily gain for lambs birth at January over rated at other month , There was a significant effect on sex of born one ( p< 0.01 ) in each birth wt. and post weaning gain where males over rated females , The results showed Regression significant ( p< 0.01 ) 6 month wt . on weaning wt. Rated 1.020 kg / kg respectively .